2020
DOI: 10.1080/22221751.2020.1738277
|View full text |Cite
|
Sign up to set email alerts
|

Competing endogenous RNA network profiling reveals novel host dependency factors required for MERS-CoV propagation

Abstract: Circular RNAs (circRNAs) are an integral component of the host competitive endogenous RNA (ceRNA) network. These noncoding RNAs are characterized by their unique splicing reactions to form covalently closed loop structures and play important RNA regulatory roles in cells. Recent studies showed that circRNA expressions were perturbed in viral infections and circRNAs might serve as potential antiviral targets. We investigated the host ceRNA network changes and biological relevance of circRNAs in human lung adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 62 publications
(84 reference statements)
1
71
0
Order By: Relevance
“…For instance, using deep sequencing of mouse lung miRNome upon SARS-CoV infection Peng and co-authors [39] showed that hsa-let-7f-5p, hsa-miR-139-3p, hsa-miR-139-5p were up-regulated directly after the infection in lung cells. A similar miRNA-seq experiment was performed on RNA isolated from Calu-3 human lung adenocarcinoma cells infected by MERS-CoV [40]. Four other miRNAs were aberrantly expressed, including down-regulated hsa-miR-98-5p as well as up-regulated hsa-miR-125a-5p, hsa-miR-125b-5p and hsa-miR-141-3p.…”
Section: Plos Onementioning
confidence: 99%
“…For instance, using deep sequencing of mouse lung miRNome upon SARS-CoV infection Peng and co-authors [39] showed that hsa-let-7f-5p, hsa-miR-139-3p, hsa-miR-139-5p were up-regulated directly after the infection in lung cells. A similar miRNA-seq experiment was performed on RNA isolated from Calu-3 human lung adenocarcinoma cells infected by MERS-CoV [40]. Four other miRNAs were aberrantly expressed, including down-regulated hsa-miR-98-5p as well as up-regulated hsa-miR-125a-5p, hsa-miR-125b-5p and hsa-miR-141-3p.…”
Section: Plos Onementioning
confidence: 99%
“…Differential expression analyses were performed using DESeq2 R package [ 37 ]. MiRNA profiling of Calu-3 (GSE139516) [ 38 ] and LF (GSE125183) [ 39 ] was performed as a part of independent experiments, limiting direct statistical comparisons between these cell lines. However, miRNAs that play important roles in the susceptibility or resistance to SARS-CoV-2 infection will likely display similar relative expression across cell lines (i.e., miRNAs important to viral susceptibility will likely be more highly expressed relative to other miRNAs in both Huh7 and Calu-3 and lowly expressed in A549 and LF) [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Specific siRNA knockdown of two taken DE circRNAs (circ-FNDC3B and circ-CNOT1) noticeably down-regulated MERS-CoV load and their target mRNA expression, thus modulating a wide variety of biological pathways, covering the ubiquitination and mitogen-activated protein kinase (MAPK) pathways. The mentioned results expound the potential host-targeting antiviral strategies for MERS-CoV infection, biological relevance of circRNAs, and ceRNA network perturbations [77]. Extents of circ_0004812 were enriched in chronic hepatitis B (CHB) cases and HBV-infected hepatoma cells.…”
Section: Circrnas In Viral and Bacterial Infectionsmentioning
confidence: 97%